Understanding Online Music Piracy Behavior via Private Communication Channels - Park, Soomin; Moon, Junghoon; Rhee, Cheul; Choe, Young Chan (Information Systems Frontiers, 2023)
In this study, we developed and tested a theoretical model to understand online music piracy behavior via email and instant messaging. We developed this theoretical model by drawing on a comprehensive literature review on music piracy, theory of reasoned action, social identity, and the deterrence theory. We collected primary data to test the hypotheses, and the results from the partial least squares analyses suggest attitude toward music file-sharing behavior and social identity positively affect intention to pirate music, whereas the perceived severity and certainty of punishment do not have significant effects on the attitude. The findings highlight the important role of social identity when a theoretical model with the concept explains music file-sharing behavior without monetary benefits in return.
Keywords: Communications channels; Deterrence theory; Digital piracy; Music file sharing; Music file-sharing behavior; Music piracy; Online music; Private communication; Social identity; Theoretical modeling; Deterrence theory; Digital piracy; Music file-sharing behavior; Social identity